FAKTOR-FAKTOR YANG MEMPENGARUHI KETERLAMBATAN PENGEMBALIAN REKAM MEDIS HIGH CARE UNIT OLEH PERAWAT DI RUMAH SAKIT TINGKAT II UDAYANA DENPASAR - Ni Putu Ulan Yunda Dewi; Agus Donny Susanto; Made Nyandra (LPPM Universitas Dhyana Pura, 2018)
ABSTRACTThe delay in returning the High Care Unit medical record is the return of medical records from the High Care Unit installation to the medical record unit in excess of the time specified in the hospital Standard Procedures Operating which is 2x24 hours. Based on preliminary observations of the data taken in September 2017, the highest percentage of the return of medical records exceeding 2x24 hours was in the High Care Unit with a total of 17 (89.5%). This study aims to determine the relationship between nurses' workloads, nurses' awards, and nurses' working conditions with the delay in returning the High Care Unit medical records by nurses at the Udayana Level II Hospital in Denpasar. The study design was quantitative analytic descriptive with cross sectional type with a sample of 14 High Care Unit nurses. The results of this study indicate that there is a relationship between the nurse workload p 0.006, the nurse award p 0.018, the working condition of the nurse p 0.040 with the delay in returning the High Care Unit medical record. The conclusions in this study indicate that there is a relationship between the workload of nurses, nurses' awards, the working conditions of nurses with the delay in returning the High Care Unit medical records.Keywords : Delay in returning the High Care Unit medical record, Workload, Award, Working ConditionsABSTRAKKeterlambatan pengembalian rekam medis High Care Unit adalah pengembalian rekam medis dari instalasi High Care Unit ke unit rekam medis melebihi waktu yang telah di tetapkan pada Standar Prosedur Operasional rumah sakit yaitu 2x24 jam semua rekam medis pasien pulang ke urusan rekam medis. Berdasarkan observasi awal data yang digunakan yaitu bulan September 2017, pengembalian rekam medis > 2x24 jam paling tinggi persentase terdapat di High Care Unit dengan 17(89,5%). Penelitian ini bertujuan untuk mengetahui hubungan beban kerja perawat, penghargaan perawat, kondisi kerja perawat dengan keterlambatan pengembalian rekam medis High Care Unit oleh perawat di Rumah Sakit Tingkat II Udayana Denpasar. Rancangan penelitian adalah deskriptif analitik kuantitatif dengan jenis cross sectional dan sampel penelitian 14 orang perawat High Care Unit. Hasil penelitian ini menunjukkan bahwa ada hubungan beban kerja perawat p 0,006, penghargaan perawat p 0,018, kondisi kerja perawat p 0,040 dengan keterlambatan pengembalian rekam medis High Care Unit. Kesimpulan dalam penelitian ini menunjukkan bahwa ada hubungan beban kerja perawat, penghargaan perawat, kondisi kerja perawat dengan keterlambatan pengembalian rekam medis High Care Unit.Kata kunci : Keterlambatan pengembalian rekam medis High Care Unit, Beban Kerja, Penghargaan, Kondisi Kerja